Outage Performance of Relay-Assisted Single- and Dual-Stage NOMA Over Power Line Communications - Roopesh Ramesh; Sanjeev Gurugopinath; Sami Muhaidat (IEEE Access, 2021)
In this paper, we analyze the performance of relay-assisted, single-stage (SS) non-orthogonal multiple access (NOMA) and dual-stage (DS) NOMA power line communication systems. Specifically, we derive closed form expressions for the outage probabilities of the SS NOMA and DS NOMA schemes. Subsequently, we formulate optimization problems and obtain closed-form solutions for the optimal power allocation coefficients of the SS NOMA and DS NOMA schemes, such that the probability of overall outage is minimized. The accuracy of our analysis and the tightness of the approximations employed are validated through Monte Carlo simulations and numerical techniques. Moreover, we show that the DS NOMA scheme outperforms the SS NOMA scheme, in terms of the overall outage probability.